Patterns of Family Upbringing and its Relationship to Perfectionism among Talented Students in Qassim Region - Yousef, Eltayb Mohammed Zaki; Almutairi, Nasser Khalaf Atallah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the relationship between the patterns of family upbringing and perfectionism among gifted students in the Qassim region, and to identify the most prominent patterns of family upbringing among the families of gifted students, and to know the prevalence of perfectionism among gifted students, and the extent of the difference in the degree of perfectionism according to the educational stage, the birth order, and the academic achievement. The descriptive correlation method was used. The sample of the study consisted of (200) male and female middle and high school students enrolled in talent schools affiliated to the Education Department in Qassim region And that is in the second and third semester of the academic year 2021-2022 AD,. To achieve the objectives of the study, two scales were developed, one of which is the scale of family upbringing patterns, which included 4 main dimensions (democracy interest, encouragement, authoritarianism cruelty, and neglect). and the measure of perfectionism in its two dimensions (adaptive and non-adaptive). The results showed that the degree of family upbringing patterns was at the average level in general, and that the degree of total perfectionism among gifted students was at the average level. The results also revealed a correlation between family upbringing patterns and perfectionism among gifted students. Adaptive perfectionism is attributed to the variable of the birth order in favor of the first-born, and there are no statistically significant differences in the non-adaptive perfectionism due to the variable of the birth order.The results also revealed that there were no statistically significant differences in adaptive and non-adaptive perfectionism due to the variable of school stage and academic achievement. In light of the findings of the study, the researcher recommends conducting more studies that investigate the relationship between the patterns of family upbringing and perfectionism among gifted students on other environments of Saudi society. It also recommends the need to provide counselling programs for families concerned with the right ways of raising children.